Midnight - Jacqueline Wilson
Violet has always been in the shadow of her mesmerising, controlling brother Will, and when a shocking secret about Will's past is revealed, things get even worse. Violet retreats further into her own fantasy world, built around the fairy characters created by her favourite author, Casper Dream. The arrival of a new girl at school, Jasmine, seems like it might change Violet's life for the better. But is Jasmine a true friend? And will Violet ever manage to break free of Will's spell?